The trajectory of cognitive decline in the pre-dementia phase in memory clinic visitors: findings from the 4C-MCI study. Issue 7 (19th November 2014) - Hamel, R.; Köhler, S.; Sistermans, N.; Koene, T.; Pijnenburg, Y.; van der Flier, W.; Scheltens, P.; Aalten, P.; Verhey, F.; Visser, P. J.; Ramakers, I.
Abstract : Background: We investigated the course of decline in multiple cognitive domains in non-demented subjects from a memory clinic setting, and compared pattern, onset and magnitude of decline between subjects who progressed to Alzheimer's disease (AD) dementia at follow-up and subjects who did not progress. Method: In this retrospective cohort study 819 consecutive non-demented patients who visited the memory clinics in Maastricht or Amsterdam between 1987 and 2010 were followed until they became demented or for a maximum of 10 years (range 0.5–10 years). Differences in trajectories of episodic memory, executive functioning, verbal fluency, and information processing speed/attention between converters to AD dementia and subjects remaining non-demented were compared by means of random effects modelling. Results: The cognitive performance of converters and non-converters could already be differentiated seven (episodic memory) to three (verbal fluency and executive functioning) years prior to dementia diagnosis. Converters declined in these three domains, while non-converters remained stable on episodic memory and executive functioning and showed modest decline in verbal fluency. There was no evidence of decline in information processing speed/attention in either group. Conclusions: Differences in cognitive performance between converters to AD dementia and subjects remaining non-demented could be established 7 years prior to diagnosis for episodic memory, with verbal fluency and executive functioning following several years later. Therefore, in addition to early episodic memory decline, decline in executive functions may also flag incident AD dementia. By contrast, change in information processing speed/attention seems less informative.